2003
DOI: 10.1074/jbc.m210552200
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 and SOCS3 Contribute to Tyr-759-dependent Attenuation of Interleukin-6 Signaling through gp130

Abstract: Interleukin-6 (IL-6) activates the Jak/STAT pathway as well as the mitogen-activated protein kinase cascade. Tyrosine 759 of the IL-6 signal-transducing receptor subunit gp130 has been identified as being involved in negative regulation of IL-6-induced gene induction and activation of the Jak/STAT pathway. Because this site is known to be a recruitment motif for the protein-tyrosine phosphatase SHP2, it has been suggested that SHP2 is the mediator of tyrosine 759-dependent signal attenuation. We recently obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(158 citation statements)
references
References 63 publications
5
153
0
Order By: Relevance
“…4 The determined affinity is in the same range of the affinity measured in a recent study reporting a K D value of 42 nM for this interaction (32). This difference may be explained by the use of peptides corresponding to the amino acid sequence of human gp130 (pY759 motif (56), amino acid sequence: ␤A-TSSTVQpYSTVVHSG) vs murine gp130 (pY757 motif, Ref. 32, amino acid sequence: acetyl-STASTVEpYSTV VHSG) and, in contrast, by differences in the experimental conditions used in both studies.…”
Section: Discussionsupporting
confidence: 70%
“…4 The determined affinity is in the same range of the affinity measured in a recent study reporting a K D value of 42 nM for this interaction (32). This difference may be explained by the use of peptides corresponding to the amino acid sequence of human gp130 (pY759 motif (56), amino acid sequence: ␤A-TSSTVQpYSTVVHSG) vs murine gp130 (pY757 motif, Ref. 32, amino acid sequence: acetyl-STASTVEpYSTV VHSG) and, in contrast, by differences in the experimental conditions used in both studies.…”
Section: Discussionsupporting
confidence: 70%
“…Promoter regions of SOCS1 and SOCS3 genes possess functional STAT binding elements and activation of JAK-STAT signaling induces rapid up-regulation of SOCS proteins by STAT-dependent pathways. In accordance with negative feedback mechanism JAK-STAT signaling is inhibited by SOCS proteins association with catalytic domains of JAKs as well as by SOCS binding to phosphorylated tyrosine residues of cytokine, GH, Prl, leptin, and erythropoietin (Epo) receptors which act as docking sites for downstream signaling [18][19][20] . STAT activation can also be inhibited by direct interaction with protein inhibitors of activated STAT proteins (PIAS) [21] .…”
Section: Wwwwjgnetcommentioning
confidence: 99%
“…There is reciprocal negative regulation of JAK-STAT3 and MAPK signaling by IL-6 [15,101,102] . SOCS3 activated by STAT3 suppresses IL-6 signaling [15,[18][19][20] .…”
Section: Developmentmentioning
confidence: 99%
“…Yoshimura and colleagues (33)(34)(35)(36) have shown that IL-6 signaling in SOCS3-deficient macrophages allows the IL-6R to generate an AIR-like inhibitory signal following LPS stimulation. SOCS3 is an inducible E3 ligase that binds to Y757 in gp130 (Fig.…”
Section: Elimination Of Socs3 Binding Allows the Il-6r To Generate Thmentioning
confidence: 99%